2016
DOI: 10.1021/acs.jmedchem.5b01913
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2/MDM2 Dual Inhibitors Based on Universal Pyramid-Like α-Helical Mimetics

Abstract: No α-helical mimetic that exhibits Bcl-2/MDM2 dual inhibition has been rationally designed due to the different helicities of the α-helixes at their binding interfaces. Herein, we extracted a one-turn α-helix-mimicking ortho-triarene unit from o-phenylene foldamers. Linking benzamide substrates with a rotatable C-N bond, we constructed a novel semirigid pyramid-like scaffold that could support its two-turn α-helix mimicry without aromatic stacking interactions and could adopt the different dihedral angles of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Both the Bim-BH3 and p53TAD α-helices project similar hydrophobic character at "hot spot" residues i, i + 3/4, and i + 7: Leu62, Ile65, and Phe69 in Bim ( Figure 1B), and Phe19, Trp23, and Leu26 in p53TAD ( Figure 1D). [44][45][46] Importantly, there is a conserved arginine residue on pro-life proteins (Arg263 in Mcl-1) that forms a salt bridge with Asp67 on the Bim α-helix at the i + 5 position. [47] Additionally, there is an aspartate residue in an analogous location (i + 2) in p53TAD (Asp21), that helps maintain the integrity of the helix rather than engage in recognition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the Bim-BH3 and p53TAD α-helices project similar hydrophobic character at "hot spot" residues i, i + 3/4, and i + 7: Leu62, Ile65, and Phe69 in Bim ( Figure 1B), and Phe19, Trp23, and Leu26 in p53TAD ( Figure 1D). [44][45][46] Importantly, there is a conserved arginine residue on pro-life proteins (Arg263 in Mcl-1) that forms a salt bridge with Asp67 on the Bim α-helix at the i + 5 position. [47] Additionally, there is an aspartate residue in an analogous location (i + 2) in p53TAD (Asp21), that helps maintain the integrity of the helix rather than engage in recognition.…”
Section: Resultsmentioning
confidence: 99%
“…The most potent inhibitor of Bcl-2, Mcl-1, and HDM2 achieved affinities of K i = 0.140, 0.161, and 0.107 μM, respectively. [45] Leveraging the successes from Novartis and Zhang with heavily functionalized pyrazoles to inhibit the Bcl-2 family of proteins and HDM2, coupled with the effective deployment of the acyl sulfonamide functional group as a carboxylic acid bioisostere in Mcl-1 inhibitors elsewhere, we designed a library of three novel, densely functionalized scaffolds to mimic the BH3 binding domain and p53TAD: isoxazoles, pyrazoles, and thiazoles ( Figure 4, right structure), which are all present in pharmacologically active drug molecules. [52][53][54][55] Each scaffold will allow us to explore the protein binding interfaces with different substitution patterns: isoxazoles represent a 1,2,3-functionalization (with the numbering starting with the acyl substituent), pyrazoles represent a 1,3,4-functionalization, and thiazoles a 1,2,4-functionalization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The pyrazole is just one of such species. They have shown extensive bioactivities, 2 such as anti-tumor, 3 antimicrobial, 4 antifungal, 5 hypoglycemic, 6 anti-inflammatory, 7 analgesic, 8 against oxidative stress and diabetes, 9 and various enzyme inhibiting activities, 10 etc. In particular, promising potentials against the malignant tumor have been demonstrated in some of modified pyrazole derivatives when they were grafted with other active groups according to the drug hybridization principle.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Currently,v enetoclax has been approved and idasanutlin (RG7388) is under clinical investigation. These agents are used to treat acute myeloid leukemia (AML) and neuroblastoma, respectively.B cl-2 family proteins and MDM2 interact similarly with p53TAD, [3] thus providing opportunities for dual Bcl-2/ MDM2 targeting with ac ombination of venetoclax with idasanutlin as an effective therapeutic strategy.R ecently, several groups have reported that these two drugs used together for the treatment of p53 wild-type acute myeloid leukemia and neuroblastoma [4] show highly synergistic antitumor activity as compared to treatment with either drug as as ingle agent. Pan et al presented am echanism for the synergistic effect in AML.…”
mentioning
confidence: 99%